2007
DOI: 10.1007/s10661-007-9807-y
|View full text |Cite
|
Sign up to set email alerts
|

Mapping giant salvinia with satellite imagery and image analysis

Abstract: QuickBird multispectral satellite imagery was evaluated for distinguishing giant salvinia (Salvinia molesta Mitchell) in a large reservoir in east Texas. The imagery had four bands (blue, green, red, and near-infrared) and contained 11-bit data. Color-infrared (green, red, and near-infrared bands), normal color (blue, green and red bands), and four-band composite (blue, green, red, and near-infrared bands) images were studied. Unsupervised image analysis was used to classify the imagery. Accuracy assessments p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Most remote sensing studies of biodiversity concentrate on trees and larger plants which can be more readily discriminated using remote sensors. In areas which have a few dominant species, such as temperate forests or mangroves, hyperspatial data have been used to delineate tree canopies and directly identify individual trees at the species level [4][5][6]. This task, challenging enough when there are a few species, becomes close to impossible when the number of species approaches the level of tens or hundreds.…”
Section: Introductionmentioning
confidence: 99%
“…Most remote sensing studies of biodiversity concentrate on trees and larger plants which can be more readily discriminated using remote sensors. In areas which have a few dominant species, such as temperate forests or mangroves, hyperspatial data have been used to delineate tree canopies and directly identify individual trees at the species level [4][5][6]. This task, challenging enough when there are a few species, becomes close to impossible when the number of species approaches the level of tens or hundreds.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown the ability to classify a variety of aquatic vegetation species using satellite imagery (Jakubauskas et al 2002, Everitt et al 2007, Silva et al 2008. Preliminary inspection of Landsat imagery indicated that it should be possible to establish not only the presence and absence information for AV (as was done in this study), but also to identify detailed spectral signatures for various species or species groups of AV.…”
Section: Future Research Opportunitiesmentioning
confidence: 66%
“…Remote sensing techniques offer rapid acquisition of data with generally short turn-around time at lower costs than ground surveys (Tueller 1982). Multispectral airborne and satellite imagery have been used extensively to distinguish and map aquatic vegetation (Carter 1982, Martyn et al 1986, Tiner 1997, Jakubauskas et al 2002, Everitt et al 2008, John 2010. Multispectral ground reflectance measurements have also been used to characterize and differentiate among wetland and aquatic plant species.…”
Section: Remote Sensing and Gis For Aquatic Plant Studiesmentioning
confidence: 99%
“…Marshall and Lee (1994) found that the process of selecting training classes and the subsequent signature evaluation needed in a supervised classification was a time consuming process. Everitt et al (2005Everitt et al ( , 2008 showed that a supervised classification does not produce significantly better results than an unsupervised classification when mapping macrophyte species. For these reasons, an unsupervised classification using the Iterative Self-Organizing Data Analysis Technique (ISODATA) algorithm was run on the study area in the WorldView-2 image in four different spectral band subsets which was decided according to band dissimilarity derived from the PCA.…”
Section: Digital Classification and Accuracy Assessmentmentioning
confidence: 99%